Effects of Cooperative Learning and Contingency Contracting on Mathematics Achievement of Pupils with Attention Deficit Hyperactivity Disorder in Warri, Nigeria (2012)
Children with Attention Deficit Hyperactivity Disorder (ADHD) and accompanying learning difficulties in mathematics experience considerable degree of helplessness as a result of their inability to successfully solve mathematical problems. The effects of ADHD on learning difficulties may become overwhelming on these pupils. This is probably caused by some personal, psycho-social and environmental factors distractive enough to negatively affect their concentration in class and achievement in mathematics. Literature substantiates the impact of utilising intervention plans to effectively manage ADHD pupils with specific learning difficulties in order to enhance their academic performance. However, there is dearth of studies that combine co-operative learning strategy and contingency contracting technique to improve the mathematics achievement of pupils with ADHD and accompanying learning difficulties in mathematics. This study, therefore investigated the effects of Co-operative Learning Strategy and Contingency Contracting Technique on mathematics achievement of pupils with ADHD in Warri, Nigeria. The study adopted pretest, posttest, control group quasi-experimental research design with a 3x2x2 factorial matrix. Multi-stage sampling technique was used to select 90 participants from three randomly selected public primary schools in the three local government areas in Warri. The participants were randomly assigned to treatment and control groups. Participants in the two treatment groups were exposed to eight weeks of Co-operative Learning Strategy and Contingency Contracting Technique. Two instruments used were: Vanderbilt ADHD Diagnostic Teacher Rating Scale (α= 0.93) and Woodcock-Johnson III Mathematics Fluency Achievement Tests Scale (α= 0.84). Seven hypotheses were tested at 0.05 level of significance and data analysed using Analysis of Covariance and Duncan post hoc. There was a significant main effect of treatment on mathematics achievement of pupils with ADHD (F (2, 87) = 127.29, p<0.05). Co-operative learning strategy was more effective in improving mathematics competence skills (= 96.6) of pupils with ADHD than contingency contracting technique. Also, age had significant main effect on mathematics achievement of pupils with ADHD (F (1, 88) = 4.65, p<0.05). However, gender had no significant main effect on mathematics achievement of pupils with ADHD. Likewise, there was no significant interaction effect of age and gender on mathematics achievement of pupils with ADHD. Furthermore, there was no significant interaction effect of treatment, age and gender on mathematics achievement of pupils with ADHD in the study. Co-operative learning strategy and contingency contracting technique were effective in improving mathematics achievement of pupils with attention deficit hyperactivity disorder. Hence, the study enlightened teachers, school authorities, parents and government of the fact that mathematics achievement of pupils with ADHD could be fostered to enhance better academic accomplishment with the use of these intervention programmes. Therefore, it is recommended that teachers of pupils with ADHD and accompanying learning difficulties in mathematics should adopt the two strategies to reinforce positive attitude to teaching learning situation of these children